Addictive Behaviors: New Readings on Etiology, Prevention, and Treatment. 2009
DOI: 10.1037/11855-015
|View full text |Cite
|
Sign up to set email alerts
|

Immediate antecedents of cigarette smoking: An analysis from ecological momentary assessment.

Abstract: It is clear that nicotine dependence is a driving motive behind tobacco use and cigarette smoking (U.S. Department of Health and Human Services, 1988). Nevertheless, deeper understanding of motivation for smoking continues to propel theoretical speculation and empirical research. In particular, a notable feature of the nicotine-dependence or nicotine-regulation model is that it does not readily account for the situational variability in smoking. Researchers have focused on the immediate motives or triggers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
188
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(215 citation statements)
references
References 68 publications
25
188
2
Order By: Relevance
“…Hazard ratios for craving, negative affect and restlessness were larger for smoking lapse than they were for ad libitum smoking. These results are consistent with findings from cruder methods of analysis, which have also concluded that negative affect is not associated with ad libitum smoking but is strongly associated with smoking lapse (Shiffman et al, 2002;Shiffman, 2005). Interpretation of this contrast is limited since mood ratings for lapse events were obtained retrospectively after the lapse, which could introduce bias.…”
Section: Is a Vector Of Time Varying Covariates Specified Insupporting
confidence: 87%
See 1 more Smart Citation
“…Hazard ratios for craving, negative affect and restlessness were larger for smoking lapse than they were for ad libitum smoking. These results are consistent with findings from cruder methods of analysis, which have also concluded that negative affect is not associated with ad libitum smoking but is strongly associated with smoking lapse (Shiffman et al, 2002;Shiffman, 2005). Interpretation of this contrast is limited since mood ratings for lapse events were obtained retrospectively after the lapse, which could introduce bias.…”
Section: Is a Vector Of Time Varying Covariates Specified Insupporting
confidence: 87%
“…Since questions focus on current psychological states, EMA avoids recall biases that are inherent in retrospective reports, and EMA avoids effects that are introduced in an artificial laboratory environment, increasing the ecological validity of the data (Shiffman and Stone, 1998). Shiffman et al (2002) and Rathbun et al (2007) investigated ad libitum (i.e. on-going, unrestricted) smoking behaviour before the quit time, finding that the momentary risk of smoking a cigarette is an increasing function of the smokers' restlessness.…”
Section: Introductionmentioning
confidence: 99%
“…The craving items reproduced in Table 3 are not specific to withdrawal craving. This is because while deprivation typically increases craving [65], craving also occurs during ongoing smoking [62,66], and predicts smoking satisfaction [67,68] and future ad libitum smoking [66,69]. Withdrawal-related craving is targeted by the recommended withdrawal criterion (see Table 3, criterion 2).…”
Section: Criterion 1: Cravingmentioning
confidence: 99%
“…As previously reported 19 , the exit cards were developed using principles of ecological momentary assessment. [20][21][22][23] EMA is frequently used in health behavior research to overcome traditional self-report assessment limitation. 21,23,24 EMA limits recall bias by being completed close in time to the exposure (ex: the dental visit) and helps with participation rates and diffusion of the intervention by being brief and unobtrusive.…”
Section: Data Collection-patient Level Exit Cardsmentioning
confidence: 99%
“…For this analysis we used baseline, prerandomization, cross-sectional data on provider performance of tobacco control. This cross-sectional study linked the baseline patient exit card data and base- (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) year olds = 37.2%) compared with older (over 60 = 23.6%) and there was a significant trend by age group (37%, 32%, 27%, and 24% respectively for those less than 30, 30-44 years, 45-60 years, and over 60 years old). A similar trend by age group was seen for ADVISE (50%, 45%, 39%, and 35%) among the 3,155 tobacco users in the sample.…”
Section: Analysesmentioning
confidence: 99%